2020
DOI: 10.9734/arrb/2020/v35i1130297
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Microbial and Sensory Characteristics of Yoghurt Processed by Adding Various Formulations of Gum Arabic and Guar Gum

Abstract: Yoghurt is one of the most popular fermented dairy products widely consumed all over the world. The present study aimed to evaluate the physicochemical, microbial and sensory characteristics of yoghurt produced by added various levels of Gum Arabic and Guar gum (stabilizers). Physicochemical characteristics, microbial characteristics and sensory evaluation of processed yoghurt samples were conducted under laboratory conditions by standard methods. The results showed that yoghurt produced by the addition of Gum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…Which can be explained by slight evaporation and decrease in moistures content as a result of the increase in acidity of the product. Similar results were obtained by Salih et al, (2020). Regarding SN%, it is obvious that the addition of WPC and AG increased SN%.…”
Section: Total and Soluble Nitrogen Percentages (Tn And Sn %)supporting
confidence: 85%
“…Which can be explained by slight evaporation and decrease in moistures content as a result of the increase in acidity of the product. Similar results were obtained by Salih et al, (2020). Regarding SN%, it is obvious that the addition of WPC and AG increased SN%.…”
Section: Total and Soluble Nitrogen Percentages (Tn And Sn %)supporting
confidence: 85%
“…Moreover, it was also evident form the results that all samples including control showed declining trend in overall acceptance scores with corresponding increases in storage period from 1 to 28 days. Similarly, in a study carried out by Salih et al ( 2020 ), whereby cow milk yogurt was evaluated for its sensory properties after addition of gum Arabic powder at range of 0.5%–1.5%. The authors reported that gum Arabic significantly ( p < .05) affected the sensory properties of yogurt 0.5% addition level of gum Arabic powder exhibited the highest score of overall acceptability.…”
Section: Resultsmentioning
confidence: 99%
“…Other synergistic effects of guar gum include its combination with protein. This combination produces heat‐stable gels and creates thicker and creamier textures in products such as yogurt and ice cream (Brennan & Tudorica, 2008 ; Lee & Chang, 2016 ; Salih et al, 2020 ). However, various variables such as the amount of gum, the amount of ingredients used in combination with gum, and the characteristics of the food product are important in the application of the synergistic effect.…”
Section: General Propertiesmentioning
confidence: 99%
“…For example, in gelled milk desserts, even low levels of GG will form a solid milk gel. Several studies suggest that GG acts as a binder in most foods and beverages, thickens liquids, and substitutes fat for a product with a similar profile (Salih et al, 2020 ). Additional information and different examples are shown in Table 1 .…”
Section: Applications Of Guar Gum In the Food Industrymentioning
confidence: 99%